3D Porphyrin-Based Covalent Organic Frameworks - Lin, Guiqing; Ding, Huimin; Chen, Rufan; Peng, Zhengkang; Wang, Baoshan; Wang, Cheng (Journal of the American Chemical Society, 2017)
The design and synthesis of three-dimensional covalent organic frameworks (3D COFs) bearing photoelectric units have been considered as a big challenge. Herein, for the first time, we reported the targeted synthesis of two 3D porphyrin-based COFs (3D-Por-COF and 3D-CuPor-COF), starting from tetrahedral (3D-T d) and square (2D-C 4) building blocks connected through [4 + 4] imine condensation reactions. On the basis of structural characterizations, 3D-Por-COF and 3D-CuPor-COF are microporous materials with high surface areas, and are proposed to adopt a 2-fold interpenetrated pts topology with Pmc21 space group. Interestingly, both 3D COFs are photosensitive and can be used as heterogeneous catalyst for generating singlet oxygen under photoirradiation. However, 3D-Por-COF shows enhanced photocatalytic activity compared with 3D-CuPor-COF, indicating the properties of 3D porphyrin-based COFs can be tuned by metalation of porphyrin rings. The results reported here will greatly inspire us to design and synthesize 3D COFs bearing other metalloporphyrins for interesting applications (e.g., catalysis) in the future.